Catalysts for money laundering and control by the banks / analytical study in the province of Arbil measures - بادواةيى, سردار عثمان; سماقةيى, ايوب انور; عمر, لقمان عثمان (Journal of Economics and Administrative Sciences, 2016)
Receive money laundering phenomenon of interest to researchers and scholars on different intellectual orientation of economic or political or other, as this process is gaining paramount importance in light of business and increase the number of banks in the province of Kurdistan of Iraq and Erbil in particular and in the presence of openness developments chaotic economic and there are no factors encourage money laundering operation because of the presence of the hidden economy and the weakness of the banking and legal measures to combat them, and on this basis there is a need to examine money laundering operation in the province of Arbil, to indicate the presence or absence of a money laundering operation in working in the province of Arbil, the banks, where the results showed a spread of this phenomenon is due to the lack of attention to the sources of funds and the existence of administrative difficulties and banking and difficulties in gathering information and weak managerial competencies and banking, as well as the lack of controls to inquire about the sources of funds, and the lack of a specific law to combat money laundering. The research found a number of recommendations that emphasize the need for the legislation of a national law to combat money laundering as well as the need to activate international cooperation in the fight against money laundering and making the most of the experiences of some developed countries.